RELEVANSI PEMIKIRAN PENDIDIKAN RIF’AT AT-TAHTAWI DALAM SISTEM PENDIDIKAN MODERN: STUDI KOMPARATIF DENGAN MODELPENDIDIKAN FINLANDIA: (The Relevance of Rif'at At-Tahtawi's Educational Thoughts in the Modern Education System: A Comparative Study With the Finland Education Model) - Muhammad Khairul Mukminin (Raqib: Jurnal Studi Islam, 2025)
This study examines the relevance of Rif'at At-Tahtawi's educational thinking in the modern education system with a comparative study of the Finnish education model. Rif'at At-Tahtawi is known as one of the reformers in the world of Islamic education who emphasizes the importance of science, inclusive education, and renewal of the learning system. Meanwhile, Finland has been recognized as a country with the best education system in the world that emphasizes equality, teacher autonomy, and skills-based learning and innovation. This study aims to analyze the similarities between the educational values ​​put forward by At-Tahtawi and the principles applied in the Finnish education system. The formulation of the problem in this study is how At-Tahtawi's thinking can contribute to the modern education system and to what extent his educational concept is relevant to the Finnish education model. The method used is qualitative research with a descriptive-comparative approach, through a literature review of At-Tahtawi's thinking and an analysis of the Finnish education system. The results of the study indicate that there are several similarities between At-Tahtawi's thinking and the principles of Finnish education, especially in the aspects of educational equality, openness to knowledge, and the importance of moral education. These findings can form the basis for educational reform in the Islamic world by adapting best practices from the Finnish system.